Electrochemical double layer capacitor based on cellulose-pva hybrid electrolyte - Ibrahim, Z.A.; Arof, Abdul Kariem; Hashim, M.A.; Majid, Siti Rohana (2005)
A polyvinyl alcohol (PVA) cellulose electrolyte was prepared by casting a solution of PVA and H3PO4 on both sides of a cellulose membrane (filter paper). The ionic species H+ are caused by the H3PO4 acid which is entrapped inside the PVA and in the pores of the filter paper. The electrolyte was sandwiched between two carbon electrodes to form an electric double layer capacitor (EDLC). The EDLC exhibits a good charge and discharge characteristics with a capacitance value of 30 Fg(-1).